Foraging deeply: Depth‐specific plant nitrogen uptake in response to climate‐induced N‐release and permafrost thaw in the High Arctic. (27th September 2020) - Pedersen, Emily P.; Elberling, Bo; Michelsen, Anders
Abstract: Warming in the Arctic accelerates top‐soil decomposition and deep‐soil permafrost thaw. This may lead to an increase in plant‐available nutrients throughout the active layer soil and near the permafrost thaw front. For nitrogen (N) limited high arctic plants, increased N availability may enhance growth and alter community composition, importantly affecting the ecosystem carbon balance. However, the extent to which plants can take advantage of this newly available N may be constrained by the following three factors: vertical distribution of N within the soil profile, timing of N‐release, and competition with other plants and microorganisms. Therefore, we investigated species‐ and depth‐specific plant N uptake in a high arctic tundra, northeastern Greenland. Using stable isotopic labelling ( 15 N‐NH4 + ), we simulated autumn N‐release at three depths within the active layer: top (10 cm), mid (45 cm) and deep‐soil near the permafrost thaw front (90 cm). We measured plant species‐specific N uptake immediately after N‐release (autumn) and after 1 year, and assessed depth‐specific microbial N uptake and resource partitioning between above‐ and below‐ground plant parts, microorganisms and soil. We found that high arctic plants actively foraged for N past the peak growing season, notably the graminoid Kobresia myosuroides . While most plant species ( Carex rupestris, Dryas octopetala, K. myosuroides ) preferred top‐soil N, the shrub Salix arctica also effectively acquired N from deeper soil layers. All plants were able to obtain N from the permafrost thaw front, both in autumn and during the following growing season, demonstrating the importance of permafrost‐released N as a new N source for arctic plants. Finally, microbial N uptake markedly declined with depth, hence, plant access to deep‐soil N pools is a competitive strength. In conclusion, plant species‐specific competitive advantages with respect to both time‐ and depth‐specific N‐release may dictate short‐ and long‐term plant community changes in the Arctic and consequently, larger‐scale climate feedbacks. Abstract : Climate warming in the High Arctic may increase soil nitrogen (N) availability, both in shallow soil layers and near the permafrost thaw front. Increased N availability could enhance plant growth and change species composition, importantly affecting the ecosystem carbon balance. We show that high arctic plants actively forage for N in the autumn, and that species differ in terms of where in the soil profile they take up N, including at the permafrost thaw front and in competition with microorganisms. Plant species‐specific competitive advantages with respect to both time‐ and depth‐specific N uptake may dictate long‐term plant community change in the Arctic.